Johann Friedrich Reichardt (1752-1814) - Bodmer, H. (artist):::Creator::::::::::::; Graff, Anton, 1736-1813 (artist):::Contributor:::::::::::: (2020)
Portrait of the composer and music writer Johann Friedrich Reichardt (1752-1814), later issue of a lithograph by H. Bodmer based on the painting by Anton Graff